Can we predict difficult laparoscopic cholecystectomy preoperatively? A comprehensive study - Jain, Yugal D.; Patel, Ravi V. (International Journal of Research in Medical Sciences, 2024)
Background: In the study, we have tried to assess some preoperative factors (history, clinical and ultrasonographic factors) that might make the laparoscopic cholecystectomy difficult. Objective was to study the predictive scoring pattern in difficult laparoscopic cholecystectomy cases. Methods: It was a prospective observational study. Ninety cases of suspected cholecystitis were identified for study presented to Jehangir hospital, Pune with upper abdominal pain or vomiting or dyspepsia or jaundice. Such patients were studied in detail clinically, admitted and investigated. Ultrasound abdomen was done in all patients. Results: Out of 90 cases studied, 64 patients (71.1%) had pre op score between 0-5 i.e. easy level, 21 patients (23.3%) had pre-op score between 6-10 i.e. difficult level and 5 patients (5.6%) had pre-op score between 11-15 i.e. very difficult level against intra-op scoring of 57 patients (63.33%) being easy, 28 patients (31.1) difficult and 05 patient (5.6%) had very difficult surgery. Conversion rate in present study to open surgery was 5.6%. For predicting easy laparoscopic cholecystectomy, accuracy of preop score was 85.6% and for predicting very difficult lap cholecystectomy, accuracy of preoperative score was 95.6%. Conclusions: Strongly significant factors predicting difficult laparoscopic cholecystectomy were number of hospitalisations, impacted stone and obesity. This study demonstrated that a scoring system predicting the difficulty in laparoscopic cholecystectomy is feasible and easy way. Identification of these factors preoperatively might help to psychologically prepare the patients for open surgery and for prolonged convalescence.